Which is better, non-fermented or fermented diets?: The case of production of broilers - Gerald M. Rivera; Leomarich F. Casinillo (Aceh Journal of Animal Science, 2021)
The broilers food was provided from  fermented and non-fermented of the raw materials. Fermentation utilizes microorganisms to transform raw materials into useful products, resulting in the production of nutritionally enriched, very stable food products from low-value carbohydrate and protein substrates. Therefore, this study aimed to assess the growth performance, return above feed cost and mortality of broilers given a non-fermented (control) and fermented feeds using plain water, water+15 ml coco vinegar and water +15 ml RPL8+AKE probiotic as fermenting agents. The fermentation process lasted for 72 hours inside tightly covered container in a dark room at room temperature. A total of 120 broiler chicks were randomly assigned to four treatment diets and were replicated three times with ten birds per replication following a Complete Randomized Design set-up. Data on cumulative weekly weight gain (CWWG), average daily gain (ADG), and feed conversion ratio (FCR) were subjected to one-way Analysis of Variance (ANOVA) and comparison between treatment means was done by Honestly Significant Difference test using the SPSS version 20.0. Results revealed a better growth performance of broilers under non-fermented diet compared with fermented diets. Significantly (p0.01) highest ADG on broilers fed with non-fermented ration (m=0.397g, sd=0.0086g), followed by water+15 ml coco vinegar (0.365g), water+15 ml RPL8+AKE probiotic (m=0.343g, sd=0.0114g) and plain water  (m=0.314g, sd=0.0057g). Although below the Philippine average (2.0) and standard (1.9) FCR, broilers fed with non-fermented diet had the better FCR (2.3) than those fed with fermented rations. The lowest feed cost and positive return above feed cost on broilers given fermented diets imply a negative impact on the expected profit in poultry production instead of non-fermented ration. However, no mortality was recorded for broilers given a fermented diets which implies that it produces vigorous broilers.